2007
DOI: 10.1161/01.res.0000258174.77370.2c
|View full text |Cite
|
Sign up to set email alerts
|

Notch Ligand Delta-Like 1 Is Essential for Postnatal Arteriogenesis

Abstract: Abstract-Growth of functional arteries is essential for the restoration of blood flow to ischemic organs. Notch signaling regulates arterial differentiation upstream of ephrin-B2 during embryonic development, but its role during postnatal arteriogenesis is unknown. Here, we identify the Notch ligand Delta-like 1 (Dll1) as an essential regulator of postnatal arteriogenesis. Dll1 expression was specifically detected in arterial endothelial cells, but not in venous endothelial cells or capillaries. During ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 33 publications
6
136
0
Order By: Relevance
“…Several studies have shown a role of the Notch and Wnt pathways in angiogenesis [42][43][44]. Notch signalling is required for angiogenesis in ischaemia models, and Dll1, the expression of which was lower in ASCs ZDF , is essential for postnatal angiogenesis [45], while jagged-1 (Jag1), which we also found downregulated, enhances angiogenesis [46]. Recent reports have underlined the important role of the Wnt system in vascular morphogenesis and in organ-specific EC differentiation [47].…”
Section: −3mentioning
confidence: 68%
“…Several studies have shown a role of the Notch and Wnt pathways in angiogenesis [42][43][44]. Notch signalling is required for angiogenesis in ischaemia models, and Dll1, the expression of which was lower in ASCs ZDF , is essential for postnatal angiogenesis [45], while jagged-1 (Jag1), which we also found downregulated, enhances angiogenesis [46]. Recent reports have underlined the important role of the Wnt system in vascular morphogenesis and in organ-specific EC differentiation [47].…”
Section: −3mentioning
confidence: 68%
“…In the vasculature, Dll1 is largely confined to the arterial endothelium, and expression is strongly upregulated during ischemia-induced arteriogenesis (Beckers et al 1999;Limbourg et al 2007). Postnatal functional studies in null mutants are precluded by the embryonic lethality of Dll1 knockout mice (Hrabe de Angelis et al 1997).…”
Section: Notch Controls Arteriogenesis In the Adultmentioning
confidence: 99%
“…In addition to its requirement for vascular development, Notch signaling is also essential for vessel homeostasis in the adult. For example, similar to Delta-like 4 (Dll4) in the embryonic vasculature, Dll1 is restricted to arterial endothelial cells in adult blood vessels, where it is required for collateral artery remodeling (Limbourg et al, 2007). Thus, Notch signaling plays a number of roles within endothelial cells to govern artery differentiation, angiogenesis, and vascular homeostasis during both embryonic and adult stages.…”
Section: Introductionmentioning
confidence: 99%